Pengaruh Penggunaan Media Buku Saku dan Metode Ceramah Sebagai Usaha Peningkatan Pengetahuan Ibu dalam Pencegahan Karies Gigi di Posyandu Kelurahan Andalas Kota Padang - Havina Yase; Sri Ramayanti; Reni Nofika (Faculty of Dentistry Universitas Andalas, 2020)
Dental caries is a common tooth problem found among children. Mother's knowledge is a factor that influences children's dental caries prevention. Various media and methods can increase knowledge, such as pocket book and lecture methods that contain material about prevention of children’s dental caries. The objective of the study is to determine the effect of using pocket book and lecture methods on mother’s knowledge about children’s dental caries in Andalas District, Padang. This study used a quasi-experimental method with a pretest-posttest design. The sample was divided into two groups with different treatment, 22 samples were given health education using pocket book and 22 samples were given health education with the lecture method. Data analysis included Wilcoxon test and Mann-Whitney test. The result of the study is there is a significant difference knowledge between before and after health education to samples used pocket book (p-value=0,01) and lecture method (p-value=0,01). There is no significant difference for both groups (p > 0.915). The conclution of the study is health education using pocket book and lecture methods can increase mother’s knowledge about children’s dental caries prevention.